2022
DOI: 10.22219/jep.v21i02.20885
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Cashless Payment System on Inflation

Abstract: The rise of transactions without using money or what is commonly referred to as cashless transactions. Cashless transactions have several advantages, namely, functional, effortless, and quick. In addition, cashless transactions get an impact on monetary policy in Indonesia. The convenience obtained when conducting cashless transactions results in the acceleration of the velocity of money. Although the number of cash transactions in the community has decreased, the rate of money creates a high intensity with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the other hand, lower interest rates can encourage individuals and businesses to opt for cashless payment methods as the cost of borrowing decreases, making digital transactions more attractive, researchers found that electronic money usage has a significant negative effect on inflation, while debit card usage has a significant positive impact. Credit card usage showed an insignificant negative effect, and the interest rate variable had a significant positive impact (Muslikhati & Aprilianto, 2022). Cashless payment records play a crucial role in shaping a firm's access to financing.…”
Section: Literature Reviewmentioning
confidence: 97%
“…On the other hand, lower interest rates can encourage individuals and businesses to opt for cashless payment methods as the cost of borrowing decreases, making digital transactions more attractive, researchers found that electronic money usage has a significant negative effect on inflation, while debit card usage has a significant positive impact. Credit card usage showed an insignificant negative effect, and the interest rate variable had a significant positive impact (Muslikhati & Aprilianto, 2022). Cashless payment records play a crucial role in shaping a firm's access to financing.…”
Section: Literature Reviewmentioning
confidence: 97%